PENINGKATAN KETRAMPILAN CUCI TANGAN MELALUI METODE PENYULUHAN DAN PRAKTIK DI RA TAHFIDZUL QURAN JAMILURRAHMAN - Isti Antari (ABDIMAS Madani, 2019)
Hands are the part of our body that most often come into contact with objects around us, and we don't know for sure whether the things we touch are guaranteed clean. Because of this, we do not know whether our hands have germs attached due to the small size of the germs. The limbs that are most often in direct contact with our hands are the mouth and nose. The schoolchildren period includes the time when they like to hold various objects for toys and then put their hands in. The aim of the dedication is to improve the hand washing skills of children in RA Tahfidzul Quran Jamilurrahman. The method used in this community service is counseling with the lecture method and hand washing demonstrations. The results of this service activity were said to be successful by showing the skills of children in RA Tahfidzul Quran being able to wash their hands properly.